Analysis of inorganic arsenic and methylarsenic in soil after derivatization by gas chromatography-mass spectrometry. - Wenzhi Zhao; Yuan Yang; Jintao Zhang; Tao Liu (PLoS ONE)
Gas chromatography-mass spectrometry (GC-MS) has been applied to the analysis of arsenic forms in water, plants, and other samples; however, it has not been used to determine the form of arsenic in soil due to the complex soil matrix. The purpose of this study was to develop an analytical method for the simultaneous determination of inorganic arsenic species (As (III) and As (V)) and monomethylarsonic acid (MMA) in soil using GC-MS. The arsenic compounds were subjected to derivatization with 2,3-dimercapto-1-propanol (BAL) and subsequently analyzed using GC-MS. The BAL volume, derivatization reaction time, and temperature were optimized using standard added soil extracts. A reaction with 150 μL of BAL at 40°C for 30 min was selected as the optimal condition for quantitative derivatization of both inorganic arsenic (iAs) and MMA. The calibration curves exhibited linearity within the range of 5-100 ng/mL for each arsenic species, with correlation coefficients exceeding 0.997. The limits of detection for each arsenic species were determined to be 0.24 ng/mL and 1.31 ng/mL, respectively. The accuracy of the method was verified by the recovery of reference samples. The recovery experiments for reference samples showed that the recovery rates for As (III), As (V), and MMA were 89.5-93.7%, 88.5-105.6%, and 90.2-95.8% respectively, with precision ranging from 4.6 to 6.5%, 2.3 to 3.8%, and 2.4 to 6.3%. These results indicate good accuracy and precision. The accuracy of this method is not significantly different from that of liquid chromatography-inductively coupled plasma mass spectrometry (p = 0.05). The optimized method was sensitive, convenient and reliable for the extraction and analysis of different arsenic species in soil samples.